Antioxidation ability of Cordyceps militaris extract and its effects on the growth of Litopenaeus vannamei shrimp - Trần, Văn Bé Năm; Lưu , Huỳnh Kim Ngân; La, Hoàng Châu; Trần, Hữu Hậu (Hue University Journal of Science: Natural Science, 2026)
This study was conducted to investigate the antioxidant capacity of a Cordyceps militaris extract and to evaluate its effect on the growth of whiteleg shrimp (Litopenaeus vannamei). The C. militaris extract was prepared by extraction with 96% ethanol for 72 hours, followed by rotary evaporation at 55°C and vacuum freeze-drying at -4°C until a constant weight was reached. Qualitative reagents were used to identify the presence of various biochemical components within the extract. The antioxidant capacity of the extract was assessed by determining the EC50 values from three methods: RP, TAC, and DPPH. Finally, the effect of supplementing the shrimp feed with the Cordyceps extract was evaluated based on shrimp size, weight, and the feed conversion ratio (FCR). The results showed a high extraction yield of 21%, and the extract contained components such as alkaloids, flavonoids, phenolics, saponins, and coumarins. The extract shows potential to support growth in whiteleg shrimp length. However, due to the short experimental period, only a trend of improved weight gain was observed. Further studies should focus on evaluating the long-term effects on the growth and innate immune system of whiteleg shrimp.